Efektivitas Komunikasi Pemasaran Terpadu PT. Bayou Berjaya Indonesia Pada Produk Snack “My Kripick” - Roemitha Marth; Mayasari, Mayasari; Oky Oxcygentri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine and understand the implementation of integrated marketing communications carried out by PT. Bayou Berjaya Indonesia as a micro, small, and medium enterprise (MSME) in marketing the snack product